Microstructure evolution and mechanical response of hetero-induced SiCp addition in Al-6061 under high strain rate compressive loading - Tahir Mehmood Bhatti; Yangwei Wang; Saeed Jamal; Mirza Muhammad Abu Bakar Baig; Fatima Shehzadi (Journal of Materials Research and Technology)
Al/SiC composites having a high-volume fraction of SiC are eye-catching materials in the automobile and aerospace industries. However, their behavior under stringent environments i.e., under high strain rate compression is much different than quasi-static compression. For such conditions, the morphology, interfacial bonding, and the fraction of the SiC play a decisive role in achieving the high performance of the Al/SiC composites. Here, in this study, we reported that a transitional effect of de-bonding and intergranular crack in SiC has occurred in Al–SiC composites having SiC particle size >0.7 μm. Below the 0.7 μm, the diffusion of the Al dislocations is characterized on the boundary of SiC along with the strong interfacial bonding. To prove it, we have fabricated an Al6061/30 vol% SiC composite through powder metallurgy route and subsequently subjected to compression in the range of strain rate 0.001–2100 s−1. In support of our observations, the microstructure was characterized by optical microscopy, scanning electron microscopy, X-ray diffraction, electron backscattered diffraction, and transmission electron microscopy analysis. The result also revealed a positive strain rate sensitivity up to a strain rate of 1800 s−1, while for 2100 s−1, the flow stress decreased, which is the cause of adiabatic temperature rise, dynamic recrystallization in Al, and massive cracks and deboning in coarse SiC particles. We also characterized that the SiC having particle size 1–4 μm showed stacking fault and dislocation induced in the SiC due to strong interfacial bonding. A quantitate analysis of dislocation was also established by using the Williamson-Hall technique which further confirmed the dislocation activity and dynamic recrystallization in 2100 s−1, characterized by EBSD and TEM. Thus, this study enables our understating that using the fine SiC particles is promising for achieving the high performance of the Al/SiC composites for use in stringent environments.